Carotid artery stenting in the first 100 consecutive patients: results and follow up. Issue 4 (1st October 2002) - Stankovic, G; Liistro, F; Moshiri, S; Briguori, C; Corvaja, N; Gimelli, G; Chieffo, A; Montorfano, M; Finci, L; Spanos, V; Di Mario, C; Colombo, A
Abstract : Background: Carotid artery stenting is now used as an alternative to surgical endarterectomy. The availability of cerebral protection systems has expanded the area of application of this procedure. Objective: To assess the feasibility, safety, and immediate and late clinical outcome in patients undergoing percutaneous carotid interventions. Methods: Between January 1999 and December 2000, 100 consecutive patients with 102 carotid artery stenoses were treated (71 men, 29 women, mean (SD) age 67 (8) years): 49 had coronary artery disease, 28 had previous stroke or transient ischaemic attack (TIA). On the basis of the Mayo Clinic carotid endarterectomy risk scale, 73 patients were grade III–IV and 13 grade VI. Results: Baseline diameter stenosis was 78.8 (10)%, with a mean lesion length of 12.6 (5.8) mm. Angiographic success was obtained in 99 lesions (97.0%) with a final diameter stenosis of 2.4 (3.5)%. Procedural success was obtained in 96 patients (96%). Selective cannulation of three carotid arteries was impossible owing to severe vessel tortuosity. Carotid stenting was performed in 97 of the treated lesions, and protection devices were used in 67 lesions. In-hospital complications occurred in seven patients (six TIA, one (category 1) minor stroke). No major stroke or death occurred. All patients were discharged from the hospital after an average of 2.5 days. At 12 (6.2) months of follow up restenosis occurred in three patients (3.4%) (one patient with carotid occlusion had TIA). Six patients had died: two from cerebrovascular events (5 and 11 months after the procedure) and four from cardiovascular causes. Conclusions: Carotid stenting appears feasible and safe, with few major complications. Long term follow up is affected by a high incidence of cardiovascular mortality.